Γδ T cells in cancer: a small population of lymphocytes with big implications. Issue 10 (10th October 2019) - Raverdeau, Mathilde; Cunningham, Stephen P; Harmon, Cathal; Lynch, Lydia
Abstract: γδ T cells are a small population of mostly tissue‐resident lymphocytes, with both innate and adaptive properties. These unique features make them particularly attractive candidates for the development of new cellular therapy targeted against tumor development. Nevertheless, γδ T cells may play dual roles in cancer, promoting cancer development on the one hand, while participating in antitumor immunity on the other hand. In mice, γδ T‐cell subsets preferentially produce IL‐17 or IFN‐γ. While antitumor functions of murine γδ T cells can be attributed to IFN‐γ + γδ T cells, recent studies have implicated IL‐17 + γδ T cells in tumor growth and metastasis. However, in humans, IL‐17‐producing γδ T cells are rare and most studies have attributed a protective role to γδ T cells against cancer. In this review, we will present the current knowledge and most recent findings on γδ T‐cell functions in mouse models of tumor development and human cancers. We will also discuss their potential as cellular immunotherapy against cancer. Abstract : γδ T cells play crucial roles in antitumor immunity but have been also linked to tumor growth. Due to their innate and adaptive features, γδ T cells also constitute attractive candidates for newly developing cancer immunotherapy. In this review, we discuss the latest findings and future directions of this conflicting but highly promising field.